(3ebGdI aj GdaUOs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd GdbjaGd jfHZi Cf jfRd Yf GdYVdI fMh GddMe hdGjaUO UjakG aEf cGf GdYUH jefJg Ch jSQJg aUO TYQI GdeHVY s
(3BNQgG (B:s
(3hCeG Cf jMd eG bO LeO ai ae GdYQHI ef GdOe HTYQg GdeHVY aEP dc CUdM JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3HGdQSGdI GdQGHYI YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs